2018
DOI: 10.1016/j.ejc.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Strong edge-colorings of sparse graphs with large maximum degree

Abstract: A strong k-edge-coloring of a graph G is a mapping from E(G) to {1, 2, . . . , k} such that every two adjacent edges or two edges adjacent to the same edge receive distinct colors. The strong chromatic index χ s (G) of a graph G is the smallest integer k such that G admits a strong k-edge-coloring.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This implies that χ ′ s (G) ≤ 6∆ − 7 for 2-degenerate graph G. Choi, Kim, Kostochka, and Raspaud [5] further improved it to χ ′ s (G) ≤ 5∆ + 1 in 2016. Many believe that the optimal bound should be 4∆ + C for some constant C, but no progress has yet been made.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that χ ′ s (G) ≤ 6∆ − 7 for 2-degenerate graph G. Choi, Kim, Kostochka, and Raspaud [5] further improved it to χ ′ s (G) ≤ 5∆ + 1 in 2016. Many believe that the optimal bound should be 4∆ + C for some constant C, but no progress has yet been made.…”
Section: Introductionmentioning
confidence: 99%
“…The strong chromatic index of a graph G $G$ is the minimum integer k $k$ such that G $G$ has a (2k) $({2}^{k})$‐packing edge‐coloring. Strong edge‐colorings were first introduced by Fouquet and Jolivet [9] and then extended by many researchers [1, 6, 7, 11, 16–21]. Therefore, one can view (1j,2kj) $({1}^{j},{2}^{k-j})$‐packing edge‐colorings, as an intermediate form of coloring between proper edge‐colorings and strong edge‐colorings.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Hocquard, Lajou, and Lužar showed that every subcubic graph is (1, 2 ) 8 -packing edge-colorable and every 3-edge-colorable subcubic graph is (1,2 ) 7 -packing edge-colorable. Furthermore, they also conjectured that every subcubic graph is (1, 2 ) 7 -packing edge-colorable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of strong edge-coloring was first introduced by Fouquet and Jolivet [9], and later it was conjectured by Erdős and Nešetřil [7] that the strong chromatic index of a graph G is bounded by 5 4 ∆ 2 if ∆ is even and 5 4 ∆ 2 − 1 2 ∆ + 1 4 if ∆ is odd. Many researchers have made progress toward this conjecture and it includes but not limited to [1,5,6,10,22,23].…”
Section: Introductionmentioning
confidence: 99%